CHP performance under the warming climate: a case study for Russia. (1st April 2022) - Klimenko, V.V.; Krasheninnikov, S.M.; Fedotova, E.V.
Abstract: Vulnerability of the cogeneration technologies towards the climate change is addressed. Climate and energy modeling approaches were combined to simulate operation of a modern binary-cycle combined heat and power (CHP) plant across Russia. It has been shown that a heating loads decrease combined with an increase of the extreme cold temperatures is determining a crucial vulnerability mechanism for CHP technologies development under the climate change. A heating load criterion was elaborated to describe a dependence of the CHP performance on the local climate conditions. The proposed criterion was applied to generalize results of the fulfilled numerical modeling. It has been found that the climate-related CHP efficiency deterioration observed since the middle of the 20th century attained 0.3–0.9% points across Russia contributing to the current crisis of the CHP technology nationwide and increasing carbon intensity of the cogeneration sector. Peak heating demand management has been discussed as a potential adaptation strategy. The CHP efficiency drop may be leveled by an adjustment of the extreme cold temperature values according to the observed climate dynamics when designing the CHP plants. Highlights: CHP plants are vulnerable towards the climate change Heating loads drop and extreme cold temperature increase are vulnerability mechanisms A heating load criterion was elaborated for CHP efficiency dependence on the climate The efficiency drop of 0.3–1 perc. points per 1 °C was observed for Russian CHP plants Peak heating demand management is a potentially effective adaptation strategy